Elementos ficcionales en la Expositio fulgenciana: Virgilio y la parodia del grammaticus (Ordia Prima, 2025)
In his Expositio virgilianae continentiae, Fulgentius the Mythographer reads and interprets Virgil’s Aeneid through an allegorical lens, rooted in etymology and guided by scriptural closure, which sanctions morality. Generally regarded as the first Christian allegory of Virgil, the work nonetheless carries a parodic tone that is often overlooked by critics in favour of a more serious reading, where didacticism is the central focus.This paper aims to analyse the narrative situation of the Expositio, assuming it is framed in a parodic-fictional scenario, constituted by a series of elements: the school of the grammaticus, its characters, its subject, and its strategies. Our second hypothesis is that this general scenario shapes the presentation of the allegorical interpretations offered by the characters of Virgil and Fulgentius regarding the Aeneid. Our final objective is to demonstrate that the Expositio is not a didactic work but rather a parodic one, and in this sense, it diverges from didactic genres and aligns more closely with the model of the Menippean satire.
Keywords: Aeneid; Fulgentius’ Expositio; parody